Effect of filtration flux on the development and operation of a dynamic membrane for anaerobic wastewater treatment. (15th September 2016) - Saleem, Mubashir; Alibardi, Luca; Lavagnolo, Maria Cristina; Cossu, Raffaello; Spagni, Alessandro
Abstract: Dynamic membrane represents a cost effective alternative to conventional membranes by employing fouling as a means of solid-liquid separation. This study evaluated the effects of initial flux on both development rate of dynamic membrane and bioreactor performance during two consecutive experiments. The dynamic membrane was developed over a 200 μm mesh and the reactor was operated under anaerobic conditions. It was found that the effect of an initial higher applied flux on dynamic membrane development was more pronounced than mixed liquor suspended solid concentration inside the bioreactor. The development of the dynamic membrane was therefore positively associated with the applied flux. The rapid development of the dynamic membrane during the second experimental run at high initial fluxes and lower MLSS concentrations also affected the performance of the bioreactor in terms of more efficient COD removal and biogas production. A major shortcoming of applying higher initial applied flux was the formation of a denser and robust dynamic membrane layer that was resistant to applied hydraulic shear to control desired permeability and thus represented an obstacle in maintaining a long term operation with sustainable flux at lower transmembrane pressure (TMP). Highlights: High initial fluxes produced a rapid development of the dynamic membrane. Fast development of the dynamic membrane was not associated to solid concentrations. Dynamic membrane was resistant to cross flow velocity used to control permeability.